Performance of missing transverse momentum reconstruction in proton-proton collisions at root s=13 TeV using the CMS detector - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Institute of Physics Publishing, 2019)
The performance of missing transverse momentum (p® miss T ) reconstruction algorithms for the CMS experiment is presented, using proton-proton collisions at a center-of-mass energy of 13 TeV, collected at the CERN LHC in 2016. The data sample corresponds to an integrated luminosity of 35.9 fb−1 . The results include measurements of the scale and resolution of p® miss T , and detailed studies of events identified with anomalous p® miss T . The performance is presented of a p® miss T reconstruction algorithm that mitigates the effects of multiple proton-proton interactions, using the “pileup per particle identification” method. The performance is shown of an algorithm used to estimate the compatibility of the reconstructed p® miss T with the hypothesis that it originates from resolution effects.